Contribution Of Banking Finance To The Development Of Micro, Small, And Medium Enterprises - Said Faisal; Hono Sejati (Publikasi Indonesia, 2023)
Banking institutions are financial intermediaries that have a very vital role in the economic structure of every country. Banks absorb funds from the public and channel these funds back to the public so that each country can create a banking system that is sound, and resilient to maintain public trust. The approach used in this research is a qualitative descriptive approach. It is focused to discuss the role of Islamic banking in contributing to developing MSMEs in Indonesia. The provision of initial capital financing and additional monetary along with facilitating and promoting MSMEs in obtaining MSME financing by Bank Syariah Indonesia plays a crucial role in the community. With the provision of financing provided by banks to the micro, small, and medium business community, Bank Syariah Indonesia can improve the economy, and the community's economy is growing and experiencing an increase in income.